2016
DOI: 10.1038/eye.2016.20
|View full text |Cite
|
Sign up to set email alerts
|

The kinetics of VEGF and MCP-1 in the second vitrectomy cases with proliferative diabetic retinopathy

Abstract: Purpose To determine whether the concentrations of vascular endothelial growth factor (VEGF) and monocyte chemoattractant protein (MCP)-1 in the vitreous changed after vitrectomy in patients with proliferative diabetic retinopathy (PDR). Participants Twenty-one eyes of 21 patients who needed a second surgery for PDR were included. The reasons for the second surgery were tractional retinal detachment (TRD), neovascular glaucoma, persistent vitreous hemorrhage, macular pucker, and secondary intraocular lens (IOL… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 24 publications
0
6
0
Order By: Relevance
“…They revealed that the MCP‐1 levels had a tendency to instantly rise subsequent to surgery and then decline with time. This study also showed that in case of a second tractional retinal detachment operation, the levels of MCP‐1 were considerably higher than those with other retinal disorders; including pars plana vitrectomy, neovascular glaucoma, macular pucker, and secondary intraocular lens implant (Sassa et al 2016).…”
Section: Mcp‐1 In Drmentioning
confidence: 62%
“…They revealed that the MCP‐1 levels had a tendency to instantly rise subsequent to surgery and then decline with time. This study also showed that in case of a second tractional retinal detachment operation, the levels of MCP‐1 were considerably higher than those with other retinal disorders; including pars plana vitrectomy, neovascular glaucoma, macular pucker, and secondary intraocular lens implant (Sassa et al 2016).…”
Section: Mcp‐1 In Drmentioning
confidence: 62%
“…Yoshida et al [ 7 ] had reported the association between MCP-1 and diabetic macular edema after PPV. There’s also evidence that the MCP-1 concentration was markedly elevated after PPV, implying an association between the prolonged inflammation after vitrectomy and complications, especially TRD [ 20 ]. We suppose that the inflammatory reaction induced by high MCP-1 might aggravate macular edema or progression of PDR, which could compromise postsurgical visual function.…”
Section: Discussionmentioning
confidence: 99%
“…Cytokine levels in VF at the time of primary vitrectomy surgeries might vary depending on the severity of diseases and timing of the surgeries. For instance, in cases with PDR, histories of anti-VEGF treatment, or laser photocoagulation might affect the results 911…”
Section: Discussionmentioning
confidence: 99%